Hemostatic Testing in Critically Ill Infants and Children - Nair, Alison B.; Parker, Robert I. (Frontiers in Pediatrics, 2021)
Children with critical illness frequently manifest imbalances in hemostasis with risk of consequent bleeding or pathologic thrombosis. Traditionally, plasma-based tests measuring clot formation by time to fibrin clot generation have been the “gold standard” in hemostasis testing. However, these tests are not sensitive to abnormalities in fibrinolysis or in conditions of enhanced clot formation that may lead to thrombosis. Additionally, they do not measure the critical roles played by platelets and endothelial cells. An added factor in the evaluation of these plasma-based tests is that in infants and young children plasma levels of many procoagulant and anticoagulant proteins are lower than in older children and adults resulting in prolonged clot generation times in spite of maintaining a normal hemostatic “balance”. Consequently, newer assays directly measuring thrombin generation in plasma and others assessing the stages hemostasis including clot initiation, propagation, and fibrinolysis in whole blood by viscoelastic methods are now available and may allow for a global measurement of the hemostatic system. In this manuscript, we will review the processes by which clots are formed and by which hemostasis is regulated, and the rationale and limitations for the more commonly utilized tests. We will also discuss selected newer tests available for the assessment of hemostasis, their “pros” and “cons”, and how they compare to the traditional tests of coagulation in the assessment and management of critically ill children.